PERANCANGAN DESTINATION BRANDING DESA WISATA PUJIHARJO KABUPATEN MALANG SEBAGAI UPAYA MENINGKATKAN AWARENESS - Wicaksono, Yohanes Anggoroadi; Martono, Siswo; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2018)
Researchers make direct observations and found that the village tourism Pujiharjo Malang regency does not have a logo that describes the potential owned and lack of supporting media to promote the village.in destination branding design, the researcher only focuses on logo and supporting media as a promotion form of Pujiharjo tourism village. the concept of a logo that has been designed is a fraternity, which in the concept describes the form of the fraternity owned Pujiharjo village. Supported media designed include brochures, banners, x-banners, and merchandise as a destination to promote the Pujiharjo tourist village in order to attract more tourists.